GROWTH OPPORTUNITY, LIKUIDITAS DAN STRUKTUR MODAL SEBAGAI DETERMINAN NILAI PERUSAHAAN INDEKS JII70 - Sinaga, Ananda Sabrida Tora Br; Yunus, Muhammad (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This study aims to determine and analyze the effect of growth opportunity, liquidity and capital structure on firm value in JII70 companies listed on the Indonesia Stock Exchange. The type of research conducted is causal associative research. The population in this study are companies listed on the Jakarta Islamic Index 70 on the Indonesia Stock Exchange in 2019-2023. The sample in this study was determined using purposive sampling technique which is a sample selection technique using certain considerations or criteria. The analysis method used in this research is Multiple Linear Regression Analysis with the help of SPSS 27 Software. The results in this study indicate that partially growth opportunity is proven to have a positive and significant influence on firm value. Capital structure is proven to have a negative and significant influence on firm value. While liquidity has no significant effect on firm value.